2023
DOI: 10.3390/ijms24043761
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Heat Shock Cognate Protein 70 Genes in Sex Determination and Differentiation of Chinese Tongue Sole (Cynoglossus semilaevis)

Abstract: Fish sex determination can be affected by environmental temperature. This process relies on temperature-sensitive proteins such as heat shock proteins (HSPs). Our previous work found that heat shock cognate proteins (HSCs) may participate in high-temperature associated sex reversal of Chinese tongue sole (Cynoglossus semilaevis). However, the role of hsc genes in responding to high temperature and affecting sex determination/differentiation remains unclear. Here, by using C. semilaevis as model, we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The PPI analysis and heat map analysis revealed that numerous genes linked to the HSP family were present in females at first 1 h to 2 h, including hsp70, hspa5, hspa41, hspb6, and hsp90. The HSP family's expression, including hsp70 and hsp90, which are modulated under high temperatures has also been reported in various other species [74][75][76][77][78][79]. Moreover, it has been reported that hsp70 and hsp90 interact with the steroid hormone receptors to allow efficient hormone binding [80,81].…”
Section: Heat Stress Upregulated Hormone-related Genes In Femalesmentioning
confidence: 87%
“…The PPI analysis and heat map analysis revealed that numerous genes linked to the HSP family were present in females at first 1 h to 2 h, including hsp70, hspa5, hspa41, hspb6, and hsp90. The HSP family's expression, including hsp70 and hsp90, which are modulated under high temperatures has also been reported in various other species [74][75][76][77][78][79]. Moreover, it has been reported that hsp70 and hsp90 interact with the steroid hormone receptors to allow efficient hormone binding [80,81].…”
Section: Heat Stress Upregulated Hormone-related Genes In Femalesmentioning
confidence: 87%
“…The testicular cell line of C. semilaevis originated from the researchers’ laboratory and was cultured in L15 compound medium at 24 °C [ 41 ]. Taking an empty plasmid as the control group, Lipofectamine 3000 Reagent (Thermo Fisher, Invitrogen, Carlsbad, CA, USA) was used to transfect the recombinant plasmid into 6-well plates.…”
Section: Methodsmentioning
confidence: 99%